Миллий концептлар тадқиқининг лингвомаданиятшуносликка доир аспектлари - Абдимуратова, К (SCIENCE and SOCIETY, 2023)
This article is a fundamental article, and we tried to analyze the theory and data on the concept of author concept from the aspects of linguistics and cognitive linguistics. The article examines the opinions of foreign and local linguists and describes them with examples.
Keywords: concept; cultural linguistics; national concept; conceptual sphere; cognitive linguistics